UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN BINAHONG (Anredera cordifolia (ten.) Steenis) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus DAN Pseudomonas aeruginosa - Ani Sulistyarsi; Nanda Wahyu Pribadi (Pharmed: Journal of Pharmaceutical Science and Medical Research, 2018)
Medicinal plants have been used from generation to generation to prevent, heal and maintain health. The aim of this research is to know the effect of binahong leaf extract (Anredera cordifolia (ten.) Steenis) on the growth of Staphylococcus aureus and Pseudomonas aeruginosa bacteria. The design of the study was a complete randomized design of 7 treatments, 3 replications. Binary extract by maceration test using ethyl acetate. The concentration of binahong extract used control (0%), 25%, 30%, 35%, 40%, 45%, 50% for Staphylococcus aureus and Pseudomonas aeruginosa bacteria. Data were analyzed by ANOVA oneway test, correlation and linear regression. The result showed that binahong against Staphylococcus aureus bacteria at 25% concentration, on bacterium Pseudomonas aeruginosa: concentration 50%. In KBM extract binahong test of Staphylococcus aureus bacteria with concentration 50%, on bacterium Pseudomonas aeruginosa with 100% concentration. ANOVA oneway test results: there is a significant difference between treatments. The value of sig (0,000) <p (0.05). The higher the concentration of binahong extract, the more able to inhibit and kill the bacteria Staphylococcus aureus (r = -0,805), Pseudomonas aureginosa (r = -0.616). The results of phytochemical tests found polyphenolic compounds, alkaloids and flavonoids